Economic and thermo-hydraulic features of multiphase nanofluids in a heat exchanger equipped with novel turbulators: A numerical study. (November 2022) - Mustafa, Jawed; Alqaed, Saeed; Sharifpur, Mohsen
Abstract: In this research study, thermo-hydraulic as well as economic analysis of three channel types, including smooth channel, the one with conventional turbulators, and that with novel turbulators were assessed. Channels contain water/aluminum oxide nanofluid with some volume fractions ranging from 1 to 4% and various diameters of nanoparticles from 20 to 50 nm when the Reynolds number changed up to 5000. Numerical simulations were performed through applying the finite volume method, the SIMPLEC algorithm and the Eulerian-Mixture Model (EMM). According to the results, using channels with turbulators could improve the Thermo-Hydraulic Performance Evaluation Criterion (THPEC). An optimal Reynolds number (Re = 5000) was found for which the highest THPEC value could be obtained. The improvement in the THPEC of the channel having the conventional turbulators was compared to the smooth one, which was 13%; meanwhile, that of the channel with innovative turbulators was improved by 23% and 10%, as compared to a smooth channel and the one having conventional turbulators, respectively. The fabrication of a heat exchanger with novel turbulators and the same energy efficiency and outlet temperature needs almost 11% less material when compared to the heat exchanger not having turbulators.